Punishment in Canada: Extending Gladue-Like Procedures to Non-Indigenous Offenders - Old, Lindsay (My University, 2021)
In the Canadian criminal justice system, there is a procedure which provides additional protections to Indigenous offenders during sentencing and its related events. This procedure is commonly referred to as the Gladue process. This thesis defends the plausibility of extending Gladue-like procedures to non-Indigenous offenders on the grounds that failing to do so would be a failure of consistency of the law. The law must be consistent in the sense that it must treat like cases alike. It will be argued in this thesis that there are other individuals and groups who may be similarly deserving of additional protections during sentencing because of their significant circumstances of vulnerability. This includes black individuals, LGBTQIA+, and mentally ill persons, but this is by no means an exhaustive list. This thesis does not aim to diminish the unique experience of Indigenous persons, but rather, it suggests that extending Gladue-like processes to particular non-Indigenous persons and groups may be required based on consistency of the law and attention to intersectionality. It is my hope that this thesis brings about greater awareness to the sentencing procedures pertaining to both Indigenous and non-Indigenous offenders alike, and that it may spark discussion on the subject of extending additional legal protections to vulnerable persons. This thesis relies heavily on the hybrid theory of punishment, as presented by H.L.A. Hart, which combines both utilitarian and retributivist elements in justifying the act of punishment. Hart’s theory aligns with the Canadian legislation on sentencing and provides a convincing justification for punishment while allowing the inclusion of restorative punishment practices for vulnerable persons. It will be argued that extending restorative practices to non-Indigenous offenders is, in some cases, plausible, and at times, necessary.
Keywords: Punishment; Criminal Sentencing; legal philosophy